2021
DOI: 10.1136/bmjopen-2020-047640
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the referral of children with severe illnesses at primary care level in Ethiopia: a cross-sectional study

Abstract: Context and objectiveEthiopia’s primary care has a weak referral system for sick children. We aimed to identify health post and child factors associated with referrals of sick children 0–59 months of age and evaluate the healthcare providers’ adherence to referral guidelines.DesignA cross-sectional facility-based survey.SettingThis study included data from 165 health posts in 52 districts in four Ethiopian regions collected from December 2018 to February 2019. The data included interviews with health extension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Our study showed that referral is initiated to avert a negative health outcome that may occur if there is a delay in referring a child for advanced care which is consistent with guidelines for the management of childhood illnesses. 27 Previous research reported that health care workers refer seriously ill children the most 41 and this may result in delayed referral of other children that are not in a serious condition which may deteriorate their health. Health care workers in our study make efforts to provide pre-referral treatment within the facility before referring the patient for further management which is consistent with previous studies where health workers administered artesunate and paracetamol before referring a patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study showed that referral is initiated to avert a negative health outcome that may occur if there is a delay in referring a child for advanced care which is consistent with guidelines for the management of childhood illnesses. 27 Previous research reported that health care workers refer seriously ill children the most 41 and this may result in delayed referral of other children that are not in a serious condition which may deteriorate their health. Health care workers in our study make efforts to provide pre-referral treatment within the facility before referring the patient for further management which is consistent with previous studies where health workers administered artesunate and paracetamol before referring a patient.…”
Section: Discussionmentioning
confidence: 99%
“…38,39 Our findings that the unavailability of resources triggers a referral is consistent with earlier findings in Malawi and other settings that showed that shortage of health workers, lack of essential equipment, and medicine stock-outs influences referrals. 17,28,41 This may mean that some of the cases being referred could have been managed at the primary facility if resources were available while the act of referral, in this case, burdens the next level of care unnecessarily. 40 The lack of resources like diagnostic equipment, drugs, health care workers, in health services is a major problem across several LMICs.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of access to medicines due to their poor availability or affordability negatively affects health service quality, equity and health outcomes in Africa in a variety of ways. Medicine affordability or availability in Africa is associated with medication adherence [ 1 3 ], prescribing decisions [ 4 – 6 ], patient choice of health facility [ 7 9 ], patient satisfaction [ 10 12 ], care seeking behavior [ 13 , 14 ], referral patterns [ 15 ], compliance with treatment guidelines [ 16 ], and health outcomes [ 1 , 17 , 18 ]. Unaffordability of medicines in the formal sector has also been shown to drive patients to informal markets where medicine quality may be poor [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lack of access to medicines due to poor availability or affordability negatively affects health service quality and equity in Africa in a variety of ways. Medicine affordability or availability in Africa has been associated with medication adherence, 1,2,3 prescribing decisions, 4,5,6 patient choice of health facility, 7,8,9 patient satisfaction, 10,11,12 care seeking behavior, 13,14 referral patterns, 15 compliance with treatment guidelines, 16 and health outcomes. 17,18,19 Unaffordability of medicines in the formal sector has also been shown to drive patients to informal markets where medicine quality may be poor.…”
Section: Introductionmentioning
confidence: 99%